Scale-up Science: uma contribuição para o desenvolvimento e crescimento sustentável de empresas de base tecnológica - Martins, Paula Salomão (2019)
Innovation has become the key word for business and national competitiveness. Being able to innovate and grow is a great challenge for start-ups or well established companies. Understanding this process and being able to interact with other agents and institutions in order to acquire the resources needed for its development can be a critical factor for business success. Thus, the intention of the thesis was to study how the external actors of the innovation ecosystem of a certain technology-based innovative business can positively impact the development and growth process of this enterprise. For this, a conceptual model, called Scale-up Science, is proposed, focusing on technology-based companies and their interaction with other actors. This model was developed based on an extensive literature review and on the implementation of an action research project, which consisted of the structuring, implementation and operation of the Post-Incubation Program of the UFRJ Science Park. It contributes to the analysis of the company’s status in the growth process, as well as serves as a guide for promotion of innovative initiatives.